Preparation, Physicochemical Characteristics and Rheological Properties of Forster (Trachiocephalus myops) Scale Collagen - Cong KE; Jianlin HE; Yushuang LI; Yan ZHENG; Xiyuan GAO; Hetong LIN; Junde CHEN (Shipin gongye ke-ji)
Fish collagen has significant market application potential, however, current fish collagen products do not meet the consumer demand. To develop new sources of collagen, Forster scales were utilized as raw material to prepare Forster scale collagen (FSC) and compared it with the rat tail type Ⅰ collagen standard as a control. Its structure was identified, and physicochemical characteristics and rheological properties were analyzed. The results indicated that FSC was a type Ⅰ collagen with a composition of [α1]2α2 and maintaining a complete triple helix structure. In the secondary structure, the proportion of α-helix was 43.59%±0.72%, indicating that FSC possessed excellent structural stability. The maximum thermogravimetric temperature of FSC was 294.81 ℃, indicating superior thermal stability. FSC had good water holding capacity (3.72±0.04 g/g) and oil absorption capacity (34.90±0.61 g/g), making it suitable for applications in cosmetics and meat processing. Rheological tests showed that FSC solution behaved as a pseudoplastic fluid exhibiting "shear thinning". At 5 ℃, the FSC solution exhibited elastic behavior, making it viable for a packaging material for cryogenic products, while at 15 ℃, it exhibited viscous behavior, suitable for production of luxury beverages. In summary, FSC shows the potential as a marketable alternative to traditional collagen sources.